Effects of Morphology, Structure and Altering Layers on the Composite Heat Resistance of Electrospun PS/PU - Emilija Zdraveva; Zenun Skenderi; Ivana Salopek Čubrić; Budimir Mijovic (Tekstilec)
Thermal insulating materials are of paramount importance in many application areas, including building construction, electronics, aerospace engineering, the automobile industry and the clothing industry. Electrospun materials are light weight with a well-controlled fibre diameter/morphology and a highly interconnected porous structure that facilitates the trapping of air and breathability. When combined with other conventional materials, they enhance the thermal insulating property of a composite structure. This study focused on electrospun single polyurethane (PU), polystyrene (PS) and layered composites thereof, in terms of heat resistance and its dependence on fibre diameter, pore area, number, thickness (solution volume) and the position of electrospun layers. It thus contributes to the field by addressing the effects of multiple parameters effect on a composite material’s heat resistance. The fibre diameter for both electrospun polymers increased significantly by increasing the concentration, while there was a generally opposite effect from increasing electrical voltage. The 10 wt% PU and 30 wt% PS used to produce the layered composites demonstrated the highest reduction of the fibre mean diameter, from (443 ± 224) nm to (328 ± 148) nm, and from (2711 ± 307) nm to (2098 ± 290) nm, respectively. Thicker PS fibres resulted in the greatest mean pore areas of (13 ± 9) µm2, while the PU mean pore areas were in the range of (2 ± 1) µm2 to (4 ± 2) µm2. Although all single and PS/PU composites demonstrated a porosity greater than 97%, their configuration in terms of number of layers, total thickness and PS and PU positioning (includes fibre diameter and pore area) affected the measured heat resistance. Single electrospun PS demonstrated a reduction in heat resistance of 0.0219 m2K/W (compared to electrospun PU) due to its thicker fibres and larger pore areas, and thus looser structure. Combining the two electrospun layers improved heat resistance up to 0.0341 m2K/W. The total heat resistance of the layered PU/PS composite was increased (up to 0.1063 m2K/W for the electrospun PS/PS/PU/PU) by increasing the number and volume of each electrospun layer solution, and by spinning the PU layer on top of the system, which resisted the heat flow due to its smaller pore areas and compact structure. These results prove that by optimizing process/structure parameters, a multi-layered material with good thermal performance can be designed to meet the requirements of a thermal insulating product.